SCIENTIFIC INITIATION OF HIGH SCHOOL: WHERE IS PHYSICAL EDUCATION? (Fiep Bulletin - online, 2020)
The aim of this article is to characterize and problematize the impact of High School Scientific Initiation (CI) on student education with the purpose of strengthening the discussion of new practices and experiences in schools, with young people as actors involved in this process. In addition, it points out the need for studies on the possible contributions of this level of research to the Physical Education area. To this end, the problem is initially delimited in a semiotic and self-organized view, and the concept of Youth Sociology is conceptualized as a valid theoretical current for understanding social phenomena specifically situated in MS Education and HF. It then analyzes 09 articles characterized as research on MS HF, published in 7 journals, selected from 425 articles, 4 dissertations and 3 theses. The results draw attention to key points in the initial formation of the researcher in the MS: orientation, writing, presentation, data collection and analysis, initiation scholarships, publication and approximation of schools with the academic environment. In conclusion, it was found that there are no studies on this subject in Physical Education and that the studies on the impact of MS on student education are incipient and have important descriptive data, but do not allow a detailed understanding to analyze how professional knowledge intervenes in this process and how innovations have proven improvements in the educational field. Therefore, there is a need for research that analyzes the impact of MS on a global scale as well as on research involving Physical Education topics, as there is a lot of such research, especially at the fairs held by FIs and it is not known what impact of studies of this level on sport, fight, dance, game, technologies in sport, among many themes in the formation of students.